KEBIJAKAN LUAR NEGERI CINA TERHADAP KOREA SELATAN: STUDI KASUS NORMALISASI HUBUNGAN DIPLOMATIK 1992 - , HALIMATUS SAKDIYAH, Prof. Dr. Ichlasul Amal, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In geopolitical strategic, since the separation between North Korea and South Korea make the condition of being dilematis or tension complexity in Eastern Asia. Thus, both countries relations was so very an antagonist, and instead it is predicted that it is difficult to build the recovery of the relation between Beijing and Seoul. As evidence, before the end of the 1980s, where China recognizes only North Korea as a single on the Korean Peninsula. However, after reform by a new leader Deng Xiaoping, through foreign policy, China more strives for the domestic affairs of which is to speed up economic growth through the agenda of modernization. Then China became changethe policy is his land, including policy is his land to South Korea. This research analyzed the changes in the attitude of foreign policy China against east asian region especially is South Korea. This research use one of the theory of international relations on foreign policy, namely neo-realism with the concept of national interests and analysis of foreign policy. Research questions filed is why China want to normalize diplomatic relations with South Korea? and how to process? This research result indicates that foreign policy China against South Korea is because there are two national interests. That is, the interests of the internal and external interests. Both interests are the interests of domestic and foreign on the basis of the interests of economic-politic as security of political system of chinese sentralistik (centralized). Political interests is a part interest that very vital in china. To maintain political stability, security China needs to secure CCP as China party that very a hierarchy. Hence, at the heart of our national interest was sake of economic and political China. Then neo-realis opining anarchi, the world is still itâs just as far as a interests can implementation from the object, then China is going to change his appeal to South Korea. In addition, if the reason is that economic development and political security domestic Chinese and the bottom line of Chinese then are conservative become cooperative to South Korea. Thus, the normalization process is to be held for the needs of domestic Chinese indirectly has forced china to normalize diplomatic relations with South Korea.